গণমাধ্যমে বাংলাদেশের মুক্তিযুদ্ধ, ষষ্ঠ খন্ড - মামুন, মুনতাসীর.; হক, আহমেদ মাহফুজুল. (ঢাকা : অনন্যা, 2016)
Articles, reports, and cartoons collected from various newspapers and news magazines on the 1971 liberation war of Bangladesh.
- v. 6. Dainika {macr}Anandab{macr}aj{macr}ara patrik{macr}a theke sa{dotb}mkalana
গ্রন্থপুঞ্জিগত নির্দেশিকা ও ইনডেক্স.
Bengali
Keywords: India-Pakistan Conflict, 1971 -- Mass media and the conflict; Bangladesh -- History -- Revolution, 1971 -- Mass media and the revolution; Bangladesh -- History -- Revolution, 1971.b